2004
DOI: 10.1021/bi048729y
|View full text |Cite
|
Sign up to set email alerts
|

Two-Site Autoinhibition of the ADP-Ribosylating Mosquitocidal Toxin (MTX) from Bacillus sphaericus by Its 70-kDa Ricin-like Binding Domain

Abstract: The mosquitocidal toxin (MTX) from Bacillus sphaericus SSII-1 is an approximately 97-kDa arginine-specific ADP-ribosyltransferase that is activated by proteolytic cleavage, thereby releasing the active 27-kDa enzyme (MTX(30-264)) and a 70-kDa C-terminal fragment (MTX(265-870)). In solution, the cleaved 70-kDa fragment is still a potent inhibitor of the ADP-ribosyltransferase activity of MTX. Here we studied the interaction of the 70-kDa fragment with the enzyme domain of MTX. Several C-terminal deletions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…7 This observation, in conjunction with the showing the three RB repeats in orange, green and blue. Note that each RB repeat has three strands in one β-sheet and the fourth strand in another β-sheet.…”
Section: Autoinhibitionmentioning
confidence: 55%
See 4 more Smart Citations
“…7 This observation, in conjunction with the showing the three RB repeats in orange, green and blue. Note that each RB repeat has three strands in one β-sheet and the fourth strand in another β-sheet.…”
Section: Autoinhibitionmentioning
confidence: 55%
“…8 Moreover, it was shown that the four RBL domains of MTX holo cause an autoinhibition that is non-competitive with respect to NAD + . 7 Here, we report the structure of MTX holo and discuss the autoinhibition as well as the association and the possible functions of the RBL domains.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations